Chemical and Morphological Constitutive Defensive Traits of Cyanobacteria Have Different Effects on the Grazing of a Small Tropical Cladoceran - Luciana Machado Rangel; Marcella Coelho Berjante Mesquita; Shara Rosa de Barros; Vinicius Neres-Lima; Michael Ribas Celano; Mauro Cesar Palmeira Vilar; Sandra Maria Feliciano de Oliveira e Azevedo; Marcelo Manzi Marinho (Toxins, 2025)
Antipredator defenses of bloom-forming cyanobacteria species maximize their fitness but can reduce carbon and energy transfer efficiency to higher trophic levels, making them a key regulator of plankton communities in eutrophic waters. We investigated the grazing responses of the tropical cladoceran Moina micrura to different strains of the cyanobacteria Microcystis aeruginosa and Planktothrix isothrix, using a good food source (green algae Mono-raphidium capricornutum) as a control. Both Microcystis strains grow as unicellular and are microcystins producers; however, this cyanotoxin was not detected on the filamentous Planktothrix strains. M. micrura ingested all cyanobacteria at reduced rates compared to single diets with Monoraphidium. In mixed diets, food type had a significant effect on grazing responses, which differed interspecifically. Planktothrix was more grazed than Microcystis strains. Feeding selectivity on Monoraphidium was negatively affected by the increase of cyanobacteria in the diet. We observed varied responses across treatments, ranging from feeding inhibition to different degrees of tolerance toward cyanobacteria, particularly in non-microcystin-producing species. We also highlight the selectivity of small tropical cladocerans, a pattern that is not yet well documented. These findings emphasize that studies incorporating phyto- and zooplankton with a history of coexistence can provide more meaningful insights into natural ecosystem dynamics.